Exploring the impact of financial exclusion on student performance and retention: A cross-sectional study at Mangosuthu university of technology (MUT). (Student's Journal of Health Research Africa, 2025)
BackgroundFinancial exclusion remains a critical barrier to student success in South African higher education, where socio-economic inequalities continue to affect access and retention. At Mangosuthu University of Technology (MUT), many students face financial hardship that limits access to essential academic resources such as textbooks, accommodation, transportation, and food. These constraints can negatively impact academic performance and increase the risk of dropout. This study explores the impact of financial exclusion on student performance and retention at MUT.MethodsA cross-sectional study using a structured survey was conducted with 220 undergraduate students, selected through stratified random sampling to ensure representation across faculties, years of study, gender, and funding status. The survey measured financial access, self-reported GPA, attendance rates, and retention intentions. Descriptive statistics and Pearson correlation analysis were used to examine the relationship between financial hardship and academic outcomes.ResultsA total of 198 students responded (90% response rate). Of these, 61% received full financial support via NSFAS, 24% were self-funded, and 15% had partial support. Among financially excluded students (self-funded or partially supported), 68% reported frequent class absenteeism due to unmet basic needs, while 43% were uncertain about completing the academic year. A statistically significant negative correlation (r = –0.51, p < 0.01) was found between financial stress and academic performance, indicating that higher financial hardship is linked to lower academic outcomes.ConclusionFinancial exclusion significantly affects academic engagement, performance, and retention among MUT students, particularly those lacking consistent financial support.RecommendationMUT should enhance its financial aid structures, introduce emergency relief funding, and strengthen coordination with external funders. Implementing early identification systems for financially at-risk students, combined with academic support interventions, could improve both performance and retention rates.
Keywords: Financial exclusion; Student performance; Academic retention; Higher education Funding support; Mangosuthu University of Technology (MUT); NSFAS; Student dropout Socio-economic inequality; Academic Access